# Aptitude - Surds and Indices - Discussion

Discussion Forum : Surds and Indices - General Questions (Q.No. 2)
2.
 If a x - 1 = b x - 3 , then the value of x is: b a
 1 2
1
2
 7 2
Explanation:

 Given a x - 1 = b x - 3 b a

 a x - 1 = a -(x - 3) = a (3 - x) b b b

x - 1 = 3 - x

2x = 4

x = 2.

Discussion:
26 comments Page 3 of 3.

Rakesh KIIT said:   1 decade ago
(a/b)^x-1=(b/a)^x-3
can be written as :

After cross multiplication :

(a)^(2x-4)=(b)^(2x-4)
=>(a/b)^(2x-4)=1
=>(a/b)^(2x-4)=(a/b)^0
=> 2x-4=0
=>x=4/2
=>x=2

Yashi Jain said:   1 decade ago
How could you add the powers when there is an = sign between the two.

(a/b)^x-1= (b/a)^x-3

* Remember, sinplification is always solved by 2 or more fraction or number or alphabet.

:If the alphabet fraction is not equal to one anthor,we have reranged it.

= (a/b)^x-1= (a/b)^-(x-3)= (a/b)^(3-x)

: Then we have to take power for simplification.

= x-1= 3-x

* When the number goes after or before '=' sign the sign changes

: Now we have to change the places.

= 2x=4
=x=2

I can not understand.